2020
DOI: 10.1101/2020.07.30.20165100
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical manifestations of patients with Coronavirus Disease 2019 (COVID-19) attending at hospitals in Bangladesh

Abstract: Bangladesh is in the rising phase of the ongoing pandemic of the coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). The scientific literature on clinical manifestations of COVID-19 patients from Bangladesh is scarce. This study aimed to report the sociodemographic and clinical characteristics of patients with COVID-19 in Bangladesh. We conducted a cross-sectional study at three dedicated COVID-19 hospitals. The severity of the COVID-19 cases was assesse… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 6 publications
1
13
0
Order By: Relevance
“…Around 9.35% of patients included in this study were asymptomatic during the initial assessment. Fever and respiratory symptoms were most common among the patients, reported in numerous other studies [21,27,28]. While several studies from China [28,29], Uzbekistan [30], and Brazil [31] reported weakness or fatigue as a common symptom, only 8% (n = 31 out of 377) of the patients reported that they experienced weakness during initial triage at the hospital.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Around 9.35% of patients included in this study were asymptomatic during the initial assessment. Fever and respiratory symptoms were most common among the patients, reported in numerous other studies [21,27,28]. While several studies from China [28,29], Uzbekistan [30], and Brazil [31] reported weakness or fatigue as a common symptom, only 8% (n = 31 out of 377) of the patients reported that they experienced weakness during initial triage at the hospital.…”
Section: Discussionmentioning
confidence: 78%
“…Although previous studies detailed the clinical presentation of hospital-admitted Reverse transcription-polymerase chain reaction (RT-PCR) positive COVID-19 patients, very few of these originate from an LMIC, and fewer still from Bangladesh [20,21]. To our knowledge, no previous study from Bangladesh has been able to present a comprehensive clinical pro le of CVOID-19 patients by examining the full suite of patients' characteristics, clinical presentation, diagnostic test results, treatment regiment, health outcomes, and any reported complications during the follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…A study of 103 RT-PCR-confirmed COVID-19 Bangladeshi patients demonstrated that 74.76% were mild, 9.71% were moderate, and 15.53% were severely ill patients. The most predominant clinical features include fever (78.6%), fatigue (68%), cough (44.7%), loss of appetite (37.9%), shortness of breath (37.9%), and anosmia (35.0%) [44]. Another study of 100 COVID-19 patients demonstrated symptoms like rhinitis (13.0%), body ache (13%), headache (12.0%), sputum (7.0%), abdominal pain (4.0%), and hemoptysis (3.0%) [45].…”
Section: Clinical Features Of Covid-19 Among Bangladeshi Patientsmentioning
confidence: 99%
“…Hypertension (34.0%) was the most prevalent comorbidities associated with the patients followed by diabetes mellitus (21.4%). Ischemic heart disease (9.7%), chronic kidney disease (7.8%), renal disease (8.0%), and asthma/COPD (6.0%) were also manifested in the patients [44]. Anosmia is another prominent feature of COVID-19 and can appear suddenly as the sole symptom of the COVID-19 patients immediately after the onset of disease [47,48].…”
Section: Clinical Features Of Covid-19 Among Bangladeshi Patientsmentioning
confidence: 99%
See 1 more Smart Citation